Integrative rDNAomics-Importance of the Oldest Repetitive Fraction of the Eukaryote Genome - Symonová, Radka (Genes, 2019)
Nuclear ribosomal RNA (rRNA) genes represent the oldest repetitive fraction universal to all eukaryotic genomes. Their deeply anchored universality and omnipresence during eukaryotic evolution reflects in multiple roles and functions reaching far beyond ribosomal synthesis. Merely the copy number of non-transcribed rRNA genes is involved in mechanisms governing e.g. maintenance of genome integrity and control of cellular aging. Their copy number can vary in response to environmental cues, in cellular stress sensing, in development of cancer and other diseases. While reaching hundreds of copies in humans, there are records of up to 20,000 copies in fish and frogs and even 400,000 copies in ciliates forming thus a literal subgenome or an rDNAome within the genome. From the compositional and evolutionary dynamics viewpoint, the precursor 45S rDNA represents universally GC-enriched, highly recombining and homogenized regions. Hence, it is not accidental that both rDNA sequence and the corresponding rRNA secondary structure belong to established phylogenetic markers broadly used to infer phylogeny on multiple taxonomical levels including species delimitation. However, these multiple roles of rDNAs have been treated and discussed as being separate and independent from each other. Here, I aim to address nuclear rDNAs in an integrative approach to better assess the complexity of rDNA importance in the evolutionary context.
Keywords: nucleolus; DNA Copy Number Variations; nuclear rDNA; fylogeneze; Cell Nucleolus; Phylogeny; Eukaryota; ribozomální DNA; rRNA; molekulární evoluce; Evolution, Molecular; GC-content; variabilita počtu kopií segmentů DNA; RNA, Ribosomal; secondary structure; genom; Animals; lidé; RNA ribozomální; Humans; zvířata; Genome; DNA, Ribosomal; buněčné jadérko